Creative market segmentation: understanding the bugs in consumer behavior. Issue 2 (27th May 2013) - Robson, Karen; Pitt, Leyland; Wallstrom, Asa; Plangger, Kirk; Mills, Adam J.
<x xml:space="preserve">Abstract</x> Marketers are concerned with the factors that shape and determine consumer behavior because an understanding of this facilitates the market segmentation that is so essential to the formulation of marketing strategy. This paper discusses why certain consumers are willing to share viral content, and argues that segmenting and targeting markets is key to the shareability (and therefore virality) of marketing messages. Physiological and biological determinants of behavior are largely overlooked in market segmentation; this paper introduces readers to the latent prevalence of a long‐lived and common brain parasite, Toxoplasma gondii, that explains a statistically significant portion of the variance in many behavioral and cultural variables. We introduce the academic marketing and public affairs community to this biological predictor and its potential effects on willingness to share viral content. Copyright © 2013 John Wiley & Sons, Ltd.